SYNTHES OF ROBUST ACTIVE SHIELDING SYSTEMS OF MAGNETIC FIELD GENERATED BY GROUP OF HIGH-VOLTAGE POWER LINES - I. B. Kuznetsov (National Technical University "Kharkiv Polytechnic Institute", 2018)
Aim. The synthesis of robust active shielding system of magnetic field, generated by group of high voltage power lines for reducing the induction of the initial magnetic field to the sanitary standards level and reducing the sensitivity of the system to variations in the plant parameters is given. Methodology. The synthesis is based on the solution of a multi-criteria stochastic game, in which the gain vector is calculated on the basis of the Maxwell equations solutions in the quasi-stationary approximation. The equilibrium state of the game is based on the stochastic multiagent optimization algorithms of the multiswarm particles. The initial parameters for the synthesis of active shielding system are the location of the high voltage power lines with respect to the protected from transmission line space, geometry and number of cables, operating currents, as well as the size of the protected space and normative value magnetic field induction, which should be achieved as a result of screening. The objective of the synthesis of the active shielding system is to determine their number, configuration, spatial arrangement, wiring diagrams and compensation cables currents, setting algorithm of the control systems as well as the resulting value of the induction magnetic field at the points of the protected space. Results. Robust active shielding system synthesis results for reduction of a magnetic field generated by group of high voltage power lines is given. The possibility of a significant reduction in the level of induction of the magnetic field source within and reducing the sensitivity of the system to variations in the plant parameters is given. Originality. For the first time carried out the synthesis of the robust active shielding systems of magnetic field generated by group of high voltage power lines within a given region of space. Practicalvalue. Practical recommendations on reasonable choice of the number and spatial arrangement of compensating cables of robust active shielding systems of the magnetic field generated by the group of high voltage power lines is given.